2015
DOI: 10.1680/jgele.15.00127
|View full text |Cite
|
Sign up to set email alerts
|

Effects of aggregate size on water retention capacity and microstructure of lime-treated silty soil

Abstract: International audienceLime treatment is a common technique of improving the workability and geotechnical properties of soils. In this study, the aggregate size effects on the water retention capacity and microstructure of lime-treated soil were investigated. Two soil powders with different maximum aggregate sizes (D max = 0·4 and 5 mm) were prepared and stabilised by 2% lime (by weight of dry soil). Soil samples were prepared by compaction at dry side of optimum water content (w = 17%) with a dry density of 1·… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 21 publications
1
22
0
Order By: Relevance
“…It is observed that the air permeability of the samples prepared with large aggregates (Dmax = 5 mm) is generally one order of magnitude higher than that of the samples prepared with smaller aggregates (Dmax = 0.4 mm). This can be ascribed to the larger macro-pores of samples S5 (Wang et al, 2015). Even though the samples prepared with different sizes of aggregates present the same air-filled porosity (Va/V), they have different pore size distributions and different shapes: in the case of S5, the large macro-pores form a better pore continuity leading to a higher air permeability, while in the case of S04, the smaller macro-pores form a more complex arrangement and lower continuity, resulting in a much lower air permeability.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…It is observed that the air permeability of the samples prepared with large aggregates (Dmax = 5 mm) is generally one order of magnitude higher than that of the samples prepared with smaller aggregates (Dmax = 0.4 mm). This can be ascribed to the larger macro-pores of samples S5 (Wang et al, 2015). Even though the samples prepared with different sizes of aggregates present the same air-filled porosity (Va/V), they have different pore size distributions and different shapes: in the case of S5, the large macro-pores form a better pore continuity leading to a higher air permeability, while in the case of S04, the smaller macro-pores form a more complex arrangement and lower continuity, resulting in a much lower air permeability.…”
Section: Discussionmentioning
confidence: 97%
“…After compaction, they were covered by wax and cured in a chamber at a temperature of 20±2 °C for 7, 28, 60 and 90 days, respectively. More details about the geotechnical properties of this silt and the detailed procedure of samples' preparation can be found in Wang et al (2015;.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Romero et al [13] explained that low water content range is related to intra and inter-cluster water, and the corresponding linear relationship between the logarithm suction and water content is controlled by the soil intra-aggregate microstructure. Wang et al [12] indicated that the aggregate size mainly affect the macro-pores (interaggregate pores) rather than the micro-pores (intraaggregate pores). In fact, different aggregate sizes form different contacts among soil aggregates and different size of inter-aggregate pores, which govern the lower suction range and air entry value.…”
Section: Discussionmentioning
confidence: 99%
“…Its main minerals are quartz (55%), kaolinite (12%), feldspars (11%), illite (10%), goethite (6.5%), montmorillonite (4%), chlorite (1%) and rutile (0.5%) [11]. More details about the geotechnical properties of this silt are indicated by Wang et al [12]. Nature soil was first air-dried, ground and passed through four target sieves in order to get four kinds of powders with different maximum aggregate sizes, namely S5, S2, S1 and S0.4 (as shown in Figure 1).…”
Section: Methodsmentioning
confidence: 99%